Food prices, energy and climate shocks in Uganda - Joseph Mawejje (Agricultural and Food Economics, 2016)
The objective of this paper is to examine the importance of energy and climate shocks in Uganda's food price processes. The unique features of this paper are threefold: first, we identify climate shocks computed as the deviations of monthly temperature and rainfall realisations from their respective long term means. Second, controlling for external and domestic shocks, we examine the possible role of energy prices in food price processes. Third, we examine these issues in a single equation model exploiting cointegration techniques and general-to-specific methods. Results indicate that energy prices have a long run cointegrating relationship with food prices. In addition, temperature shocks are more important than rainfall shocks in explaining food price variability.
Keywords: 330; Food prices; Energy; Climate shocks; Uganda